Q: 5 square root of 3 2 square root of 3?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

5 square root 7 because 3 square root of 28 goes from 3 square root of 28 to 3 square root of 7 and 4 which then 4 condenses down to 2 and you add that to 3 then you get 5 square root of 7

I will use "root" as a symbol for square root. I assume you want to get rid of the square root in the denominator; this will usually bring some square root into the numerator.If you have the square root by itself, or as a factor, multiply numerator and denominator by this square root. Example:3 / root(2) = 3 x root(2) / root(2) x root(2) = 3 x root(2) / 2.If the square root is added or subtracted with something else, multiply with a "complement", as in the following example:1 / root(2) + 5The "complement" is the same expression, but changing the plus sign to a minus sign. Multiply numerator and denominator aby root(2) - 5:root(2) - 5 / (root(2) + 5)(root(2) - 5)= (root(2) - 5) / (2 - 25)= (root(2) - 5) / -23= -(root(2) - 5) / 23

Multiply everything by the square root of 3 minus the square root of 2 and then times that by 100 - 72 and divide that by 5

2.5

√3 = 1.73205081√5 = 2.23606798

Related questions

-2 and -3Check:(-2) + (-3) = -5(-2)(-3) = 6Thus -2 and -3 are not the required numbers. let's find them: x + y = -6xy = -5 y = -x -6x(-x - 6) = -5-x^2 - 6x = -5x^2 + 6x = 5x^2 + 6x + 9 = 5 + 9(x + 3)^2 = 14x + 3 = (+ & -)square root of 14x = -3 (+ & -)square root of 14x = -3 + square root of 14 or x = - 3 - square root of 14y = -x - 6y = 3 - square root of 14 - 6 or y = 3 + square root of 14 - 6y = -3 - square root of 14 or y = -3 + square root of 14Check:(-3 + square root of 14) + (-3 - square root of 14) = -6(-3 + square root of 14)(-3 - square root of 14) = -5 ?(-3)^2 - (square root of 14)^2 = -5 ?9 - 14 = -5Check also tow other numbers.

sqrt(4) = 2 sqrt(9) = 3 Therefore, the square root of 4 plus the square root of 9 is equal to 2 + 3 = 5.

24

It is 2*sqrt(5).

5 square root 7 because 3 square root of 28 goes from 3 square root of 28 to 3 square root of 7 and 4 which then 4 condenses down to 2 and you add that to 3 then you get 5 square root of 7

Square root of 2, square root of 3, square root of 5, pi, e

I will use "root" as a symbol for square root. I assume you want to get rid of the square root in the denominator; this will usually bring some square root into the numerator.If you have the square root by itself, or as a factor, multiply numerator and denominator by this square root. Example:3 / root(2) = 3 x root(2) / root(2) x root(2) = 3 x root(2) / 2.If the square root is added or subtracted with something else, multiply with a "complement", as in the following example:1 / root(2) + 5The "complement" is the same expression, but changing the plus sign to a minus sign. Multiply numerator and denominator aby root(2) - 5:root(2) - 5 / (root(2) + 5)(root(2) - 5)= (root(2) - 5) / (2 - 25)= (root(2) - 5) / -23= -(root(2) - 5) / 23

It is 5/6*sqrt(3).

if you take out the word ''quantity'' your answer is 25.02725024

3 square root of 5 cannot be rationalised.3 square root of 5 cannot be rationalised.3 square root of 5 cannot be rationalised.3 square root of 5 cannot be rationalised.

Multiply everything by the square root of 3 minus the square root of 2 and then times that by 100 - 72 and divide that by 5

Let (x1, y1) = (-2, 0) and (x2, y2) = (5, 3). Distance between two points = square root of [(x2 - x1)2 + (y2 - y1)2] = square root of [(5 - -2)2 + (3 - 0)2] = square root of (72 + 32) = square root of 58